Enhanced and speedy energy extraction from a scaled-up pressure retarded osmosis process with a whale optimization based maximum power point tracking - Chen, Yingxue; Vepa, Ranjan; Shaheed, Mohammad Hasan (Energy (Oxford), 2018)
This paper proposes a novel maximum power point tracking scheme for efficient and speedy extraction of maximum power from a pressure retarded osmosis process subject to rapid salinity variation. The scheme is designed using the Whale Optimization with Differential Evolution algorithm, a nature-inspired metaheuristic technique. The algorithm has facilitated the developed maximum power point tracking controller with features that have helped overcome limitations such as lower tracking efficiency and steady state oscillations as encountered in the conventional methods. Previously, a number of widely used algorithms including perturb & observe, incremental mass resistance and mass feedback controller were used to design maximum power point control schemes for a PRO process to reduce power loss due to rapid salinity variation. However, in using these techniques, a trade-off between the oscillations and the respond time was required to adjust the operation. The proposed scheme is used to solve this problem and is implemented in simulation on a scaled-up PRO system. The performance of the scheme is compared with some popularly used maximum power point tracking controllers. It is observed from results that the proposed method not only outperforms other widely used methods but is also more robust. •A novel maximum power point tracking approach for a pressure retarded osmosis process is proposed.•The technique guarantees maximum power extraction in the face of rapid salinity variation.•The method is based on the Whale Optimization with Differential Evolution algorithm.•The method is able to overcome lower tracking efficiency and steady state oscillations.•The efficacy and robustness of the scheme are evaluated with a scaled-up PRO system.